Stock Price Determination of Consumer Goods Companies on the Indonesia Stock Exchange: Financial Ratio Analysis 2019-2023 - Raodahtul Jannah (Department of Economics Education, Faculty of Economics, Universitas Negeri Makassar, 2025)
This study aims to analyze the effect of financial ratios on stock prices in manufacturing companies in the goods and consumption sub-sector listed on the Indonesia Stock Exchange (IDX). The financial ratios used include Return on Equity (ROE), Earning Per Share (EPS), Debt to Equity Ratio (DER), and Capital Intensity. The background of this study is based on the importance of investors' understanding of company financial information as a basis for investment decision-making. This study uses a quantitative approach with a comparative causal research design. The study population includes 49 manufacturing companies in the goods and consumption sub-sector listed on the IDX, and through purposive sampling, 17 companies were obtained as samples for the period 2019–2023. Data analysis was performed using descriptive tests, classical assumption tests, and simple regression tests processed using SPSS version 23. The results show that the ROE and DER variables do not have a significant effect on stock prices, while the EPS and Capital Intensity variables have a significant effect on stock prices. These findings indicate that investors place greater consideration on a company's ability to generate earnings per share and the efficiency of fixed asset utilization when assessing stock performance. This study is expected to contribute to investors, company management, and academics in understanding the financial factors that influence stock prices in the goods and consumption sector.